2u-u+1=0

Simple and best practice solution for 2u-u+1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2u-u+1=0 equation:


Simplifying
2u + -1u + 1 = 0

Reorder the terms:
1 + 2u + -1u = 0

Combine like terms: 2u + -1u = 1u
1 + 1u = 0

Solving
1 + 1u = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 1u = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 1u = 0 + -1
1u = 0 + -1

Combine like terms: 0 + -1 = -1
1u = -1

Divide each side by '1'.
u = -1

Simplifying
u = -1

See similar equations:

| 3x^2-8x=-7 | | (4/13)/(5/12)= | | x^2-8x+y^2+4y-30=0 | | x+12=8x-2 | | x-6=1x-14 | | 37*x+(1-x)*35=35,5 | | 2/3x-1=11 | | 54-6x=12x-24 | | xx=5x | | 13-8x=10x-23 | | 5x+12=-44-10x | | 105-4x=2x-21 | | 9x+2=7x-12 | | -35-5x=13-10x | | c/2=9 | | X=3200*.80 | | 8.4=128 | | x+2-6x=x-9 | | 3-0.3k=3 | | -x+9=30 | | ((5y-2)/8)=(2+(y/4)) | | x+2-6x=x-(9-5x) | | 2z+4z=5z-4 | | 216x^6+1/64 | | 6t-t-4=4t-5 | | 6x+x-8=6x+3 | | (x-1)(x-1)(x-1)=y | | 2g(g+7)= | | H(4-5h)= | | x^3-7x=0 | | 6/z-4.4=0.4 | | x^1/2/x^3/4 |

Equations solver categories